2021
DOI: 10.29145/jmr/82/04
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Role of Moral Identity in the Relationship between Ethical Leadership and Unethical Behavior of Employees: Evidence from the Oil and Gas Sector of Pakistan

Abstract: This study draws on social identity, social learning, and trait-activation theories to probe if moral identity mediates the relationship between ethical leadership and unethical behavior. It investigates how ethical leadership serves as a predictor of employees’ unethical behavior and moral identity as a mediator between ethical leadership and employees’ unethical behavior. Together, these variables influence the self-reported unethical behavior of employees. The findings of this study are based on a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Looking at these two components of ethical leaders traits, behaviors and actions in organizations, it is argued here that when leaders abide by these traits and behaviors and act same in their relationship with subordinates, it makes employees to be more close to the leader(s), replicate them and become more affiliated to the organization and consequently generate more OCBs. Additionally, previous studies on ethical leadership and OCBs (Aloustani et al, 2020;Khan et al, 2017;Nemr and liu, 2021) found significant positive link between ethical leadership and OCBs. Moreover, SLT illustrates that ethical leaders are likely to influence their subordinates/followers in organization to engage in OCBs when they consider their leaders' behaviors as attractive and worthy of copying as role models.…”
Section: Ethical Leadership and Ocbsmentioning
confidence: 74%
See 4 more Smart Citations
“…Looking at these two components of ethical leaders traits, behaviors and actions in organizations, it is argued here that when leaders abide by these traits and behaviors and act same in their relationship with subordinates, it makes employees to be more close to the leader(s), replicate them and become more affiliated to the organization and consequently generate more OCBs. Additionally, previous studies on ethical leadership and OCBs (Aloustani et al, 2020;Khan et al, 2017;Nemr and liu, 2021) found significant positive link between ethical leadership and OCBs. Moreover, SLT illustrates that ethical leaders are likely to influence their subordinates/followers in organization to engage in OCBs when they consider their leaders' behaviors as attractive and worthy of copying as role models.…”
Section: Ethical Leadership and Ocbsmentioning
confidence: 74%
“…, 2014), Iraqi (Al-Halbusi et al. , 2021b), Pakistan (Khan et al ., 2017), Turkey (Yeşiltaş and Tuna, 2018), Malaysia (Al-Halbusi et al. , 2021a), Iran (Aloustani et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations